2019
DOI: 10.1111/apa.14692
|View full text |Cite
|
Sign up to set email alerts
|

Infants who die in shared sleeping situations differ from those who die while sleeping alone

Abstract: Aim To determine whether there are differences between infants who are sharing a sleeping surface with others, compared to those who die alone. Methods A literature review was undertaken of PubMed and Google Scholar databases using search terms: sudden infant death syndrome, SIDS, co‐sleeping and overlaying. Results Statistically significant differences were found between the two groups in the sex ratios, and in staining of brain sections for β‐amyloid precursor protein (β‐APP), glial fibrillary acidic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Although the mechanisms underlaying SUDI aren't totally understood and are still subject of exploration (4)(5)(6), medical research has highlighted a triple risk model that increases the risk of death (7). This model associates: a period of physiological maturation at risk with, in particular, the development of respiratory control, heart rate, and sleep; various respiratory diseases, especially infectious, cardiac, respiratory, responsible for an overstimulation of the immune system; an inappropriate environment related to sleeping conditions, smoking or ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms underlaying SUDI aren't totally understood and are still subject of exploration (4)(5)(6), medical research has highlighted a triple risk model that increases the risk of death (7). This model associates: a period of physiological maturation at risk with, in particular, the development of respiratory control, heart rate, and sleep; various respiratory diseases, especially infectious, cardiac, respiratory, responsible for an overstimulation of the immune system; an inappropriate environment related to sleeping conditions, smoking or ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that infants who die while sleeping with others differ from infants who die sleeping alone. A mini‐review by Collins‐Praino and Byard reports that neuropathological studies have indicated that babies who died while sleeping alone showed evidence of repeated episodes of brain injuries. In contrast, infants who died while sharing sleeping surfaces, such as their parents’ bed, appear to have experienced a more rapid death, consistent with overlaying.…”
Section: Infants Who Died During Shared and Solo Sleeping Situations mentioning
confidence: 99%
“…An important development in recent years, however, has been the demonstration that infants who die in shared sleeping situations are different epidemiologically and pathologically to those who die on their own i.e. classic SIDS deaths [7]. The male to female ratio is similar in shared sleepers demonstrating that for some reason there is a significantly higher number of girls than typical SIDS populations [8].…”
mentioning
confidence: 99%